A Pilot Study Assessing the Potential Role of non-CD133 Colorectal Cancer Stem Cells as Biomarkers - Langan, Russell C. (Ivyspring International Publisher, 2012)
Introduction: Over 50% of patients with colorectal cancer (CRC) will progress and/or develop metastases. Biomarkers capable of predicting progression, risk stratification and therapeutic benefit are needed. Cancer stem cells are thought to be responsible for tumor initiation, dissemination and treatment failure. Therefore, we hypothesized that CRC cancer stem cell markers (CRCSC) will identify a group of patients at high risk for progression. Methods: Paraffin-embedded tissue cores of normal (n=8), and histopathologically well-defined primary (n= 30) and metastatic (n=10) CRC were arrayed in duplicate on tissue microarrays (TMAs). Expression profiles of non-CD133 CRCSC (CD29, CD44, ALDH1A1, ALDH1B1, EpCam, and CD166) were detected by immunohistochemistry and the association with clinicopathological data and patient outcomes was determined using standard statistical methodology. An independent pathologist, blinded to the clinical data scored the samples. Scoring included percent positive cells (0 to 4, 0 = <10%, 1 = 10 - 24%, 2 = 25 - 49%, 3 = 50 - 74%, 4 = 75 - 100%), and the intensity of positively stained cells (0 to 4; 0 = no staining, 1 = diminutive intensity, 2 = low intensity, 3 = intermediate intensity, 4 = high intensity). The pathologic score represents the sum of these two values, reported in this paper as a combined IHC staining score (CSS). Results: Of 30 patients 7 were AJCC stage IIA, 10 stage IIIB, 7 stage IIIC and 6 stage IV. Median follow-up was 113 months. DFI was 17 months. Median overall survival (OS) was not reached. Stage-specific OS was: II - not reached; III - not reached; IV - 11 months. In a univariate analysis, poor OS was associated with loss of CD29 expression; median OS, 32 months vs. not reached for CSS 3-7 vs. >7.5, respectively; p=0.052 comparing entire curves, after adjustment. In a Cox model analysis, loss of CD29 exhibited a trend toward association with survival (p=0.098) after adjusting for the effect of stage (p=0.0076). Greater expression of ALDH1A1 was associated with increasing stage (p=0.042 over stages 2, 3b, 3c, and 4) while loss of CD29 expression exhibited a trend toward being associated with stages 3 and 4 (p=0.08). Compared to normal colon tissue, primary tumors were associated with increased expression of ALDH1B1 (p=0.008). ALD1H1B1 expression level differed according to whether the tumor was moderately or poorly differentiated, well differentiated, or mucinous; the highest expression levels were associated with moderately or poorly differentiated tumors (p=0.011). Lymph node metastases were associated with a trend toward decreased expression of EpCAM (p = 0.06) when comparing 0 vs. 1 vs. 2+ positive lymph nodes, as was CD29 (p = 0.08) when comparing 0 vs. any positive lymph nodes. Compared to normal colon tissue metastatic colon cancers from different patients were associated with increased ALDH1B1 expression (p=0.001) whereas CD29 expression was higher in normal colonic tissue (p=0.014). Conclusion: CD29 may be associated with survival as well as clinical stage and number of lymph nodes. ALDH1B1 expression was associated with differentiation as well as type of tissue evaluated. ALDH1A1 was associated with clinical stage, and decreased EpCAM expression was found in patients with advanced lymph node stage. CRCSCs may be useful biomarkers to risk stratify, and estimate outcomes in CRC. Larger prospective studies are required to validate the current findings.